The Impact of Capital Structure, Liquidity, And Firm Size OnFinancial Performance an Empirical Study Of Technology Companies Listed on The Indonesia Stock Exchange (2020 - 2023) - Roma Simbolon; Thomas Sumarsan Goh; Arthur Simanjuntak; Duma Megaria Elisabeth (Program Studi Akuntansi Universitas Simalungun, 2025)
In the era of globalization and evolving economic factors, Indonesian businesses must demonstrate resilience within increasingly competitive environments. Corporate financial health serves as a critical indicator of operational efficiency, asset utilization effectiveness, business outcome realization, outstanding obligations management, and potential bankruptcy risks. Developing internal capabilities through technological advancement, product quality enhancement, human resource development, expenditure efficiency, and performance optimization represents a strategic approach to maintaining and improving corporate financial wellness. According to research by Sarwindah and Imronudin (2023), financial performance analysis seeks to evaluate how effectively a corporation adheres to appropriate and accurate principles when conducting its financial activities